Welfare of calves and heifers on dairy farms with cow-calf contact rearing or early separation - Rademann, Anna; Schneider, Marie Louise; Waiblinger, Susanne (Frontiers in Veterinary Science, 2025)
Early separation (ES) of cow and calf in dairy farming is increasingly questioned due to implications on animal welfare. The aim of this study was to compare the welfare of animals on commercial dairy farms with cow-calf contact (CCC) or ES using a comprehensive welfare assessment protocol. We hypothesized that the welfare of calves and heifers on CCC farms is better than the welfare of those on ES farms. Fifty Austrian dairy farms, 25 practicing CCC and 25 ES, were visited. The Welfare Quality® (WQ) Protocol for dairy calves and heifers was used to assess animal welfare. The two rearing systems were compared using a t-test for qualitative behavior assessment (QBA) scores, a Mann–Whitney U Test for quantitative behavioral indicators, prevalences of clinical scoring, management parameters, and Criterion and Principle scores, and a Fisher Exact Test for dichotomous variables (occurrence yes/no) and overall classification. CCC calves and heifers scored higher in QBA (calves: p < 0.001, heifers: p = 0.022). CCC calves showed a lower frequency of non-nutritive oral behaviors (p = 0.038). Both CCC calves and heifers had more space (calves and heifers: p < 0.001), were less often disbudded (calves: p = 0.002, heifers: p = 0.003) and had more access to pasture (p < 0.001). Fewer CCC farms had calves with lesions (p = 0.049) and heifers with overgrown claws (p = 0.017). Accordingly, rearing systems differed in Criterion and Principle scores. Both CCC calves (p = 0.011) and heifers (p = 0.043) scored higher in “Appropriate Behavior” and calves scored higher in “Good feeding” (p = 0.047) and “Good housing” (p = 0.001). CCC farms had a better WQ classification than ES farms for calves (p = 0.023), and 20% or 26% of CCC farms reached “excellent” for calves or heifers compared to 0 or 12%, respectively . The better welfare of CCC animals may be related to contact to cow(s) but also to other management practices that emphasize animals’ physical and behavioral needs more. Holistic practices prioritizing animal welfare including CCC systems should be considered in the transition toward more sustainable farming.